How do natural hazards cascade to cause disasters? - AghaKouchak, Amir; Huning, Laurie S.; Chiang, Felicia; Sadegh, Mojtaba; Vahedifard, Farshid; Mazdiyasni, Omid; Moftakhari, Hamed; Mallakpour, Iman (Nature (London), 2018)
Track connections between hurricanes, wildfires, climate change and other risks, urge Amir AghaKouchak and colleagues. Track connections between hurricanes, wildfires, climate change and other risks, urge Amir AghaKouchak and colleagues.